2010
DOI: 10.1159/000321376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Low-Protein Diet Supplemented with Keto Acids on Hyperphosphatemia in Maintenance Hemodialysis Patients

Abstract: Aim: To evaluate the effects of short-term restriction of dietary protein intake (DPI) supplemented with keto acids on hyperphosphatemia in maintenance hemodialysis (MHD) patients. Methods: Forty MHD patients with uncontrolled hyperphosphatemia were randomized to either low DPI with keto acid-supplemented (sLP) or normal DPI (NP) group for 8 weeks. After 8 weeks, the sLP group was shifted to NP for another 8 weeks. Low-protein diet (LPD) was individualized with total caloric intake 30–35 kcal/kg/day, protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Moreover, studies of supplemental [36] and early parenteral nutrition [37] have delivered contradictory findings. Thus, it is not surprising that our understanding of optimal protein intake in renal disease, which is limited in patients with chronic kidney disease [38], in those on chronic dialysis [39], and in patients receiving continuous or intermittent extended RRT [40,41,42] generates great variability in feeding practices in ICU [20,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies of supplemental [36] and early parenteral nutrition [37] have delivered contradictory findings. Thus, it is not surprising that our understanding of optimal protein intake in renal disease, which is limited in patients with chronic kidney disease [38], in those on chronic dialysis [39], and in patients receiving continuous or intermittent extended RRT [40,41,42] generates great variability in feeding practices in ICU [20,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed that the excessive daily protein intake was one of the important reasons for high incidence of hyperphosphatemia in such a group of patients. Li et al recently showed that 2-month restriction of dietary protein intake (0.8 g/kg per day) supplemented with keto acids significantly decreased serum phosphate levels in anuric MHD patients with refractory hyperphosphatemia, and did not induce malnutrition (37). Although protein intake is recommended to be 1.2 g/kg per day in MHD patients by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative guidelines (38), the optimal protein intake may also need to be individualized in different patients, especially for patients without RRF and treated with a low dose of dialysis (39).…”
Section: Discussionmentioning
confidence: 99%
“…The role of animal-derived proteins in human nutrition has been reassessed in recent years, yet this critical analysis has not been fully extended to CKD and dialysis patients, for whom the equation “high quality protein = animal-derived protein = best protein” is still the basis for prescription, even if the interest on plant-based diets in all CKD stages is increasing [106,107,108,109,110,111,160,161,162]. …”
Section: Diet and Dialysis: Four Paradoxesmentioning
confidence: 99%
“…A more liberal intake of plant-derived phosphate, together with attention to avoiding food additives, is probably compatible with good metabolic control and less need for phosphate binders, which account for a relevant portion of the pill burden in dialysis patients [160,161,162,163,164,165,166,167]. The awareness that hyperphoshatemia reflects a variety of nutritional and non-nutritional derangements can guide tailored interventions [167] (Figure 3).…”
Section: Diet and Dialysis: Four Paradoxesmentioning
confidence: 99%